2020
DOI: 10.3389/fpsyg.2020.575167
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Factors Linked to Academic Performance in PISA 2018 Through Data Mining Techniques

Abstract: International large-scale assessments, such as PISA, provide structured and static data. However, due to its extensive databases, several researchers place it as a reference in Big Data in Education. With the goal of exploring which factors at country, school and student level have a higher relevance in predicting student performance, this paper proposes an Educational Data Mining approach to detect and analyze factors linked to academic performance. To this end, we conducted a secondary data analysis and buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 63 publications
3
26
0
2
Order By: Relevance
“…Home possession (HOMEPOS) and learning time in mathematics (MMINS) were two covariates selected by all approaches, indicating that the social-economic status (SES) of students and learning time in math had an important impact on the improvement of mathematics capacities. These results are consistent with prior literature (e.g., Gamazo & Martínez-Abad, 2020;Kalaycıoğlu, 2015;Lee & Stankov, 2018).…”
Section: Resultssupporting
confidence: 93%
“…Home possession (HOMEPOS) and learning time in mathematics (MMINS) were two covariates selected by all approaches, indicating that the social-economic status (SES) of students and learning time in math had an important impact on the improvement of mathematics capacities. These results are consistent with prior literature (e.g., Gamazo & Martínez-Abad, 2020;Kalaycıoğlu, 2015;Lee & Stankov, 2018).…”
Section: Resultssupporting
confidence: 93%
“…Many researchers have found that students’ achievement motivation is closely and positively correlated with academic performance ( She et al, 2019 ; Gamazo and Martínez-Abad, 2020 ). Various constructs of motivation such as perceived control, values, and self-perception can be used as a supplement to intelligence tests to positively predict the academic performance ( Daniels and Dueck, 2022 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The negative results of teenagers (< 18) were in concordance with the low scores in science obtained by Spanish students, significantly below the 2019 OECD average (Ministry of Education and Professional Training 2019) (see Online Resource 1). It has been addressed that these low academic results were highly related to the national socioeconomic circumstances of the time (Gamazo and Martínez-Abad 2020), which worsened during the 2008 crisis and its subsequent austerity policies (compare in Fig. 1c the National and Castilla-La Mancha expenditure diagrams, also see The Local 2019).…”
Section: Age Disparitymentioning
confidence: 99%